Efficacy of Anethole on Biofilm Formation, Ergosterol Content, and Cell Surface Hydrophobicity of Candida Glabrata Isolated from Urinary System - Hamid Haji Gholamreza; Aghil Sharifzadeh; Hojjatollah Shokri; Jalal Hasan (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Resistance to synthetic antifungal agents is a considerable health problem nowadays. Therefore, it is necessary to identify new antifungal molecules, such as natural products, to develop new therapeutic strategies to prevent and eradicate candidiasis. The aims of this work were to study the effect of anethole on growth, cell surface hydrophobicity, ergosterol content, and biofilm formation of Candida glabrata (C. glabrata) isolated from the urinary system. Materials & Methods: The disc diffusion method (susceptibility to synthetic antifungals), the broth micro-dilution method (susceptibility to anethole), the MTT reduction assay (biofilm formation), the HPLC technique (ergosterol content), and adherence to n-hexadecane (cell surface hydrophobicity; CSH) were employed to determine the effect of anethole against C. glabrata isolates. Statistical analysis of the data was performed using GraphPad Prism V.9, employing the one-way ANOVA test and pairwise comparisons using the Tukey test/post-hoc ANOVA at a significance level of 0.05. Results: The range of MIC of C. glabrata was 1250-5000 µg/ml for anethole (3375±1375 µg/ml). The percentages of CSH were significantly in groups treated with MIC/2 (24.73±6.37%) and MIC/4 (29.01±6.61%) concentrations of anethole. Also, the percentage changes in membrane ergosterol were 23.35% at 0.125 µg/ml, 46.46% at 0.25 µg/ml, and 73.92% at 0.5 µg/ml of anethole, compared to the control that wasn't treated. Conclusion: The results showed the effectiveness of anethole against planktonic and sessile cells of C. glabrata isolates and the interference with ergosterol content, CSH, and biofilm formation, reinforcing the potential of this natural compound as a natural antifungal.